Human Battery for Indian Defence Force - Manochandar, T; Selvan, D Siva; Sudharsan, S (International journal of electronics communication and computer engineering, 2013)
The Peltier effect can also be reversed and used to generate power in conditions where there are differences in temperature. All of these established scientific facts can be used to produce power from any thing where there are two different sources of temperatures. With the help of Inverse Peltier effect, Zigbee smart wearable physiological parameters monitoring device has been developed and reported in this paper. The system can be used to monitor physiological parameters, such as temperature, pressure and heart rate, of a human subject. Using several sensors to measure different vital signs, the person is wirelessly monitored. For achieving this, the power produced by using the human body heat and the Peltier effect will be stored in a capacitor acting as a battery and when required this power can be used for communication and other purposes also.